PRESENT-DAY METHODOLOGICAL APPROACHES TO DEFINING REGIONAL SOCIAL STANDARD OF LIVING - Лапушняк, Мирослава (Human Geography Journal, 2014)
The article represents the analysis of present-day methodological approaches to defining social standard of living in a region. The analysis disclosed debatable instants of choosing common criteria and indices for the assessment of said standard as well as it showed the problems of modern methods adaptation to available national statistical base and specific aspects of development in this or that region or settlement. The article considers trends in scientific-methodical approaches to development of integral index of social standard of living.